Experimental double random phase encoding technique under a joint transforms correlator architecture - Barrera, John Fredy (2013)
We present a review for updating the last contributions in the field of optical encoding techniques using a joint transform correlator architecture. We focus on the experimental aspects with special reference to both photorefractive and digital based applications. We describe the usual situation involved in developing the experimental set-ups when these techniques are used in multiplexing encrypted data. We address the solution to cross talk and overlapping issues associated with the multiplexing handling.